GENDER-RELATED DIFFERENCE IN JOINT HYPERMOBILITY AMONG SCHOOL-AGED CHILDREN: A DESCRIPTIVE STUDY - Sudaryanto, Wahyu Tri; Ayuningrum, Ika Yuli; Putri, Dylla Ramadhani (Akademi Keperawatan Karya Bhakti Nusantara, Magelang, Indonesia, 2023)
Joint hypermobility is common among school-aged children and it may progressively lead to joint pain and developmental delay. Identifying joint hypermobility in school-aged children would facilitate the monitoring of early changes and planning for early rehabilitative intervention. This study aimed to describe gender-related difference in joint hypermobility among school-aged children. A descriptive study was conducted in an elementary school in Surakarta, Central Java, Indonesia. The study subjects were 261 students aged 6 to 12 years selected randomly. The study variables were gender and joint hypermobility. Beighton scale was used to assess joint hypermobility score. Gender-related difference in joint hypermobility among school-aged children was tested using t-test. The results of ≥4 points on Beighton scale was observed in 157 of 261 school-aged children (60.2%). Mean of Beighton score in female children (Mean= 3.87; SD= 0.19) was higher than male chidren (Mean= 4.15; SD= 1.82), but it was statistically non-significant (p= 0.256). It can conclude that there is no difference between gender in joint hypermobility among school-aged children. The need for joint hypermobility screening tests in elementary school children is highlighted.